Do Turkish Nursing and Midwifery Students Teach Breast Self-Examination to Their Relatives ? - (:unkn) unknown (ASIAN PACIFIC ORGANIZATION CANCER PREVENTION, 2011)
Aim: To describe health beliefs and breast self-examination (BSE) practice of Turkish female nursing and midwifery students and extent of teaching the screening method to their mothers, sisters and relatives. Design: In this definition survey, data were obtained from 113 nursing and midwifery students (n = 113) in third and fourth class and their mothers, sisters and other relatives in Turkey. Methods: Data were collected using a personal data form, a knowledge evaluation form for BSE (Maurer 1997) and the Champion's Health Belief Model Scale. Number percentage, Chi-square test were used in the evaluation of the data. Results: Students learned breast cancer and BSE in their lessons one or two years previously. Knowledge level scores of the students were 52.3 +/- 9.6 (min:25,max: 75). Rate of having regular BSE was 32.7%. When health belief scale assessed; the average of susceptibility was 7.52 +/- 2.62, seriousness was 21.8 +/- 5.30, benefit was 16.7 +/- 4.45, barrier was 22.3 +/- 6.44, confidence was 40.3 +/- 6.67 and medical motivation was 26.6 +/- 4.22. The rate of having regular BSE and benefit, barrier scores were compared, they were statistically significant difference(p<0.05). The majority (106, 91.3%) gave BSE training to their mother and sisters, and 42.6% (48) to relatives, 6.2% (7) to friends, and 5.4% (6) to patients. Conclusions: Knowledge about breast cancer and BSE repetition training programs should be planned for nursing/midwifery students, to increasae their sensitivity, beliefs and attitudes, and medical motivation for BSE.
Keywords: BSE; Turkish nursing/midwifery students; attitutes; teaching to others; PEER EDUCATION MODEL; ADAPTATION; BELIEFS; SCALE; WOMEN